IMGT, the international ImMunoGeneTics database. - Giudicelli, V (1997)
IMGT, the international ImMunoGeneTics database, is an integrated database specializing in immunoglobulins, T-cell receptors (TcR) and major histocompatibility complex (MHC) of all vertebrate species, initiated and co-ordinated by Marie-Paule Lefranc, CNRS, Montpellier II University, Montpellier, France (lefranc@ligm.crbm.cnrs-mop.fr). IMGT includes two databases: LIGM-DB (for immunoglobulins and TcR) and MHC/HLA-DB. IMGT comprises expertly annotated sequences and alignment tables. LIGM-DB contains more than 19 000 immunoglobulin and TcR sequences from 78 species. MHC/HLA-DB contains class I and class II human leukocyte antigen alignment tables. An IMGT tool, DNAPLOT, developed for immunoglobulins, TcR and MHC sequence alignments, is also available. IMGT works in close collaboration with the EMBL database. IMGT goals are to establish a common data access to all immunogenetics data, including sequences, oligonucleotide primers, gene maps and other genetic data of immunoglobulins, TcR and MHC molecules, and to provide a graphical user-friendly data access. IMGT will have important implications in medical research (repertoire in autoimmune diseases, AIDS, leukemias, lymphomas), therapeutical approaches (antibody engineering), genome diversity and genome evolution studies. IMGT can be accessed at http://imgt.cnusc.fr:8104 and http://www.ebi.ac.uk/IMGT